Rotational Analysis of Femur and Tibia with Bilateral Lower Extremity Computed Tomography Measurements: A Retrospective Study - Albert Çakar; Barış Acar; Özgür Doğuş Gözlü; Ekremcan Karaer; İbrahim Taşkın Rakıcı (İstanbul Medical Journal)
Introduction: This study aimed to emphasize the importance of assessing and correcting rotational alignment of the lower extremities after trauma. To examine the effects of differences in femoral and tibial rotation on optimal patient outcomes. Methods: This single-center retrospective study was conducted at University of Health Sciences Turkey, İstanbul Training and Research Hospital in accordance with the guidelines of the Declaration of Helsinki. The study involved 130 patients who underwent lower extremity computed tomography (CT) angiography or venography between May 2015 and December 2022. Patients underwent CT scan in the supine position with their legs extended. Radiographic parameters were measured digitally, and femoral and tibial rotation angles were calculated. Results: The mean femoral and tibial rotations were 12.2° and 31.3°, respectively. No significant difference was observed between femoral and tibial rotations in terms of sex. There was a moderate correlation in femoral rotation and a high correlation in tibial rotation between the right and left sides. Conclusion: Gender was not a significant factor in the assessment of lower extremity rotational alignment. The importance of considering bilateral differences during surgical procedures is emphasized. These findings may help clinicians make more informed decisions when assessing and treating patients. However, further research is required before these findings are fully integrated into clinical practice.